Manajemen Perubahan Organisasi Sebagai Upaya Mewujudkan Bisnis Berkelanjutan - Adi Winata Kusuma Praja; Retno Purwani Setyaningrum (Jurnal Ekonomi Syariah Pelita Bangsa, 2023)
VUCA world has inspired companies to be aware of the importance of the sustainability both for the companies and the surrounding environment. The success of the companies depend on their dynamic and innovative adaptation toward changes. For that reason, the company management needs to have certain approaches in planning the changes because they don't happen abruptly. The objective of this research is to analyze the changes in the organizations / companies in their attempt to achieve sustainable business. The research applied qualitative method by collecting data through depth interviews with five company managers who have worked for at least five years. The analysis if the data was conducted through triangulation forms of documentation, interviews and direct observation in the field through case studies. The result of the research shows that companies need to conduct changes in their organization because those changes will support innovation. However, evaluation prior to those changes is necessary because the changes contribute significantly in the realization of sustainability in business as revealed in the interviews.